The Effect Of Liquid Organic Fertilizer On Shrimp Waste To The Growth And Yield Of Peanut On Peat Soil - Iponi Asri; Putu Dupa Bandem; Maulidi . (Jurnal Sains Pertanian Equator, 2019)
The aim of this research is to find out the best concentration liquid organic fertilizer on shrimp waste on peanut on peat soil. The research was conducted from 13 april to 13 july 2019 in Jl. Perdana, Gg. Mufakat 1. The study used a completely randomized design (CRD) method in which the application of organic fertilizer as a single factor. The treament were designed in five level of  concentration and 5 treatments with 5 replications and each replication consisted of 4 sample plants. The treatment in question is k1 = 20 ml/ liter of water, k2 = 40 ml/ liter of water, k3 = 60 ml/ liter of water, k4 = 80 ml/ liter of water and k5 = 100 ml/ liter of water. The observed variables in this study are plant height (cm), root volume (cm3), the dry weight of the plant (g), wet stover weight on top of plant (g), wet stover weight on bottom of plant (g), the number of pods per plant, the dry weight of pods per plant (g) and dry weight of kernel per plant (g). The results showed that the using of liquid organic fertilizer on shrimp waste with dose 60 ml/liter can improve to growth and yield of peanut on peat soil. Key word : peat soil, liquid organic fertilizer, peanut, shrimp waste.